Women Teaching for Social Change in Adult Education: The Spiritual and Cultural Dimensions of "Teaching Across Borders" - Elizabeth J. Tisdell (Adult Education Research Conference, 1999)
This study is an exploratory look at understanding how spirituality is renegotiated and informs the emancipatory work of a purposeful sample of women activist adult educators.